2003
DOI: 10.1007/s00421-003-0818-2
|View full text |Cite
|
Sign up to set email alerts
|

Finger cold-induced vasodilation: a review

Abstract: Cold-induced vasodilation (CIVD) in the finger tips generally occurs 5-10 min after the start of local cold exposure of the extremities. This phenomenon is believed to reduce the risk of local cold injuries. However, CIVD is almost absent during hypothermia, when survival of the organism takes precedence over the survival of peripheral tissue. Subjects that are often exposed to local cold (e.g. fish filleters) develop an enhanced CIVD response. Also, differences between ethnic groups are obvious, with black pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
248
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(264 citation statements)
references
References 86 publications
13
248
3
Order By: Relevance
“…In this case the cooling is so fast that the withdrawal criteria were reached by cooling of the superficial skin before cooling could affect the deeper skin layers. Cold induced vasodilation (CIVD) was not a concern for any of the conditions tested as maximal test duration for this study was 3 minutes, CIVD is typically not observed for 5-10 minutes after the start of local cold exposure of the extremities (Daanen, 2003).…”
Section: Discussionmentioning
confidence: 98%
“…In this case the cooling is so fast that the withdrawal criteria were reached by cooling of the superficial skin before cooling could affect the deeper skin layers. Cold induced vasodilation (CIVD) was not a concern for any of the conditions tested as maximal test duration for this study was 3 minutes, CIVD is typically not observed for 5-10 minutes after the start of local cold exposure of the extremities (Daanen, 2003).…”
Section: Discussionmentioning
confidence: 98%
“…The emergence of CIVD has been described as nonsystematic, and, hence, its function(s) as well as its causative agent(s) remain unexplainable (10,11,40). We recently proposed that CIVD is a thermoregulatory mechanism triggered by increased mean body temperature (19).…”
mentioning
confidence: 99%
“…The lower the temperature, the more marked the reaction was. Most experiments conducted since this time has used water temperatures of 0, 5 or 8°C to evoke CIVD (Daanen 2003).It is also possible to evoke CIVD responses using exposure to cold air. Kramer and Schulze (1948) observed that the timing of the CIVD responses was similar for ice water bath immersion and exposure to ¡18°C air in a still air box.…”
mentioning
confidence: 99%
“…The lower the temperature, the more marked the reaction was. Most experiments conducted since this time has used water temperatures of 0, 5 or 8°C to evoke CIVD (Daanen 2003).…”
mentioning
confidence: 99%